THE ROLE OF EMPATHY ON BEHAVIORAL AND EMOTIONAL STRENGHT AMONG ISLAMIC PRESCHOOLERS: PARENTS AS RESPONDENTS - Rizkyanti, Charyna Ayu (Asosiasi Psikologi Islam (API) Himpsi, 2017)
Preschool age is a special time where children develop their ability in controlling emotion and behavior. Empathy is one of the most important virtues encouraged in Islam, which helping the children to manage themselves. This basic human capacity could be identified in a very early age. However, many environmental factors may diminish the children’s empathy that actually is still flourishing. This research investigated the effect of the empathy on the emotional-behavioral strength among preschool children in Islamic Kindergarten, Jakarta, through parents’ reports. There were 107 out of 150 parents completed two types of questionnaires. The Empathy Questionnaire (EmQue) measures three aspects in young children: (a) emotion contagion, (b) attention to other’s feelings, and (c) prosocial actions; while PreBers Scale assessed the Emotional and Behavioral strength by four facets (a) emotional regulation, (b) school readiness, (c) social confidence, and (d) family involvement. The result indicated that empathy has significant effects on behavioral and emotional strength among preschoolers. Based on this finding, parents should nurture their child’s empathy to help them see from the point of views of others.